Simulador háptico para entrenamiento médico en cirugías de trauma ortopédico (2017)
The immersive haptic training is an option to train orthopedic residents who need to acquire experience in a orthopedic trauma surgery, since the orthopedic training is only given during a surgical preccedure. This undergraduate project presents an application developed in Unity which can simulate the fracture fragments location as well as the force required to realice the reduction process with a Phantom Omni per hand. It provides also different visual tools which cannt not be learned during a real surgery: different planes location at the same time or gap distance between a 100%-well-done reduction. In the same way the tool can objectivelly feedback about the performance based on surgical (theorical knowledgmentes) or psycomothors metrics. The test phase applied to orthopedist and residents prooves a shock with a first use with the haptic device for training. However they assure the application has power to training for a first orthopedic trauma surgery approach.